IMPROVING STUDENTS’ SPEAKING ABILITY THROUGH ROLE PLAY AND PICTURE AND PICTURE AT SMP NEGERI 1 RATAHAN - Tini Mogea (Pusat Riset dan Inovasi Nasional, 2023)
The purpose of this research is to prove whether role play and picture-in-picture are effective or not in improving students’ speaking abilities at SMP Negeri 1 Ratahan. This research is classified as